Temporal trends in serum concentrations of polychlorinated dioxins, furans, and PCBs among adult women living in Chapaevsk, Russia: a longitudinal study from 2000 to 2009 - Burns Jane S; Birnbaum Linda S; Emond Claude; Williams Paige L; Korrick Susan A; Altshul Larisa; Sergeyev Oleg; Humblet Olivier; Lee Mary M; Revich Boris; Shelepchikov Andrey; Feshin Denis; et al. (BMC, 2011)
Abstract Background The present study assessed the temporal trend in serum concentrations of polychlorinated dibenzo-p-dioxins, dibenzofurans, and biphenyls (PCBs) among residents of a Russian town where levels of these chemicals are elevated due to prior industrial activity. Methods Two serum samples were collected from eight adult women (in 2000 and 2009), and analyzed with gas chromatography-high-resolution mass spectrometry. Results The average total toxic equivalency (TEQ) decreased by 30% (from 36 to 25 pg/g lipid), and the average sum of PCB congeners decreased by 19% (from 291 to 211 ng/g lipid). Total TEQs decreased for seven of the eight women, and the sum of PCBs decreased for six of eight women. During this nine year period, larger decreases in serum TEQs and PCBs were found in women with greater increases in body mass index. Conclusions This study provides suggestive evidence that average serum concentrations of dioxins, furans, and PCBs are decreasing over time among residents of this town.